Marmara Üniversitesi Prof. Dr. Orhan Oğuz Kütüphanesi’nde Element Konsantrasyonları - GÜNEŞ, GÜSSÜN; BOZKURT KOPUZ, ESİN (My University, 2018)
Solunabilir temiz havanın her geçen gün insan sağlığı açısından önemi artmaktadır. İnsan yaşam süresinin çoğunluğunun ev, okul,iş mekanlarının iç ortamında geçtiği düşünüldüğünde binalardaki yetersiz hava kalitesinin insan sağlığına zararı bugün daha fazlabilinmektedir. Günümüzde özellikle iç hava kalitesi ve binalardaki partiküler madde (PM10, PM2,5 ve PM1) konusunda birçok bilimselçalışma bulunmasına rağmen, özelikle mekân olarak kütüphane binalarında iç hava kalitesinin element konsantrasyonuna ilişkin bilimselçalışmalara pek rastlanmamaktadır. İnsan sağlığı açısından zararlı olan bu elementler literatürde metal ve yarı metaller olarakadlandırılmaktadır. Genellikle ağır metaller olarak gruplandırılmaktadır. Ağır metaller insan sağlığı açısından vücutta biriktiğindetoksik etki gösterebilen metal elementlerdir. Uluslararası Kanser Araştırmaları Ajansı (IARC), alüminyum (Al), kobalt (Co), bakır(Cu), demir (Fe), nikel (Ni) ve çinko (Zn)’yu kanserojen olmayan elementler olarak, arsenik (As), kadmiyum (Cd), krom (Cr) vekurşun (Pb)’u hem kanserojen hem de kanserojen olmayan elementler olarak sınıflandırılmıştır. Arsenik, kurşun, kadmiyum, nikel,civa, krom gibi ağır metaller kansere neden olabilecek ve insan sağlığına zarar verebilecek yaygın çevre kirleticileridir. Bu çalışmanınamacı Marmara Üniversitesi Prof. Dr. Orhan Oğuz Kütüphanesi’nde iç ortam hava kalitesi incelenerek partikül maddedeki elementkonsantrasyonları ölçümlenerek, partiküler maddelerin fiziksel özellikleri ile metal element konsantrasyonları içerikleri analizedilmiştir. Analizler için havadaki 10 mikrondan küçük çaptaki partiküller 05.01.2014-31.12.2014 tarihleri arasında yirmi dörtsaatlik PM10 ve PM2,5 örnekleri olarak toplanmıştır. Çalışmamızda PM10 (166 günlük örnek) ve PM2,5 (170 günlük örnek) ortam kütlekonsantrasyonu, gravimetrik yöntemle belirlenmiştir. Elde edilen ölçüm sonuçlarının element analiz sonuçları değerlendirildiğinde;ölçüm yapılan kütüphane binasında PM10 filtrelerinin metal değerleri sırasıyla Na 0-1710, Mg 0-716, Al 14-1967, K 100-622, Ca955-3943, V 0-99, Cr 0-1120, Mn 14-100, Fe 304-4644, Co 1-4, Ni 13-490, Cu 13-61, Zn 48-603, As 0,4-121, Se 3-9, Cd 6,7-6,7, Pb26-1042ng/m³ arasında değiştiği, PM2,5 filtrelerinin ise Na 0-1133, Mg 0-720, Al 14-1047, K 0-388, Ca 0-2992, V 0,4-90, Cr 0-1328,Mn 0-121, Fe 0-4340, Co 0,4-3, Ni 0-551, Cu 0-39, Zn 0-1606, As 3,9-104, Se 2-16, Cd 0-392, Pb 0-347ng/m³ arasında değiştiğigözlemlenmiştir. Uluslarası literatürle ve Dünya Sağlık Örgütü limit değerleriyle kıyaslandığında element konsantrasyonlarının genellikledüşük olduğu gözlenmiştir. Trafik kaynaklı (Cr ve Pb), toprak kaynaklı (Al) elementlerin ve Na, Ca, Fe elementleri ise yüksekkonsantrasyon olduğu ölçümlenmiştir. Kütüphanenin giriş ana kapısı, iki çalışma salonu ve internet-DVD salonu girişlerindengeçen kişi sayıları arasındaki Pearson korelasyonları değerlendirildiğinde oldukça yüksek çıkmıştır. İnternet-DVD salonuna girenkişi sayısı ile diğer kapı girişlerindeki kişi sayıları arasındaki korelasyon diğerlerine göre daha düşük olmasına rağmen yine de yüksekilişkilidir. Element konsantrasyonları (PM10, PM2,5) ve kütüphaneye giren kişi sayıları arasında zayıf ilişki olduğu 0,3’den küçükPearson korelasyonu ile belirlenmiştir. Faktör hesabı sonucu topraktan kaynaklanan ve denizden kaynaklanan etki incelenmiştir ve toprak kaynaklı etkinin daha fazla olduğu görülmüştü.

The importance of respirable clean air in terms of human health is a matter of increasing concern. Most of an individual’s life is spent in indoor spaces at home, at school, or at the workplace and it is now recognized more than ever that a substandard quality of air in buildings has a harmful impact on human health. Today, despite the fact that there are many scientific studies on the subject of indoor air quality and particulate matter (PM10, PM2.5 and PM1 ), only a few articles of scientific research can be found on element concentrations in the context of indoor air quality in especially spaces such as library buildings. Elements can be harmful to human beings and to environmental health and these are classified as metals and semimetals, generally grouped together as heavy metals. As far as human health is concerned, heavy metals are metal elements that may cause a toxic effect when accumulated in the body. The International Cancer Research Agency (IARC) classifies aluminum (Al), cobalt (Co), copper (CU), iron (Fe), nickel (Ni) and zinc (Zn) as noncarcinogenic elements and arsenic (As), cadmium (Cd), chrome (Cr) and lead (Pb) as both carcinogenic and noncarcinogenic elements. Arsenic, lead, cadmium, nickel, mercury, chrome and other similar heavy metals are potentially harmful to human health in that they may cause cancer and are also widespread polluters of the environment. This study was conducted at Marmara University’s Prof. Dr. Orhan Oğuz Library, where the air quality of the indoor environment was analyzed through measurements of element concentrations in particulate matter; the analysis encompassed the physical properties of the particulate matter and the content of the metal element concentrations. Toward this aim, particles of air in the indoor environment of the library building with diameters smaller than 10 microns were collected as 24-hour PM10 and PM2.5 samples over the period January 5, 2014 – December 31, 2014. The PM10 (166-day sample) and PM2.5 (170-day sample) mass concentrations in the environment in our study were determined using a gravimetric method. In the evaluation of the outcome of the element analysis based on the results of the measurements obtained, it was observed that the metallic values of the PM10 filters varied as follows: Na 0-1710, Mg 0-716, Al 14-1967, K 100-622, Ca 955-3943, V 0-99, Cr 0-1120, Mn 14-100, Fe 304-4644, Co 1-4, Ni 13-490, Cu 13-61, Zn 48- 603, As 0,4-121, Se 3-9, Cd 6,7-6,7, Pb 26-1042ng/m³, and that the PM2.5filters varied as follows: Na 0-1133, Mg 0-720, Al 14- 1047, K 0-388, Ca 0-2992, V 0,4-90, Cr 0-1328, Mn 0-121, Fe 0-4340, Co 0,4-3, Ni 0-551, Cu 0-39, Zn 0-1606, As 3,9-104, Se 2-16, Cd 0-392, Pb 0-347ng/m³. When compared to international literature and World Health Organization limit values, element concentrations were generally low. While concentrations of Na, Ca, Mg, Al, K were higher in Guangzhou, Mumbai and Zhenbeitai, they were lower in Quito than values in the Marmara University Library. Furthermore, Ca concentrations in Doha and Ahmeabad and Al concentrations in Ahmeabad, Pune, Tel Shikmona and Erdemli were higher than values in Marmara University Library. The concentrations of As, V, Se, Cd, Cr, Mn, Fe, Pb, Co, Ni in Quito were lower, only Cu concentration was higher than values in the Marmara University Library. While Zn concentrations in Guangzhou, Mumbai and Ahmeabad were higher, they were lower in Zhenbeitai, Pune, Tel Shikmona and Erdemli than values in the library. Fe and Pb concentrations in Mumbai, Zhenbeitai, Ahmeabad, Pune, Tel Shikmona and Erdemli were higher but Fe concentration was lower in Guangzhou than values in the library. Cu concentrations in Guangzhou, Quito and Pune were higher than in the library, but the concentrations of Cr in Guangzhou, Tel Shikmona and Erdemli were lower. The measurements showed that there were high concentrations of traffic-related (Cr and Pb) and soil-related (Al) elements as well as of the elements Na, Ca and Fe. A high value was found when Pearson’s correlation was used to assess the number of people passing through the library’s main entrance, its two study room entrances and the Internet-DVD room entrance. Although the correlation between the number of people entering the Internet-DVD room and the number passing through the other entrances was lower than the others, the correlation was still strong. The value of less than 0.3 that was found with Pearson’s correlation indicated a weak correlation between element concentrations (PM10, PM2.5) and the number of people entering the library. Factor calculations showed that in an examination of soil-related and sea-related impacts, the soil-related impact was stronger.
Element Concentrations in Marmara University Dr. Orhan Oğuz Library
Keywords: Kimya, Analitik; Kimya, Uygulamalı; Kimya, İnorganik ve Nükleer; Kimya, Tıbbi; Kimya, Organik; Çevre Bilimleri; Matematik; Fizik, Matematik; Mühendislik, Kimya; Mühendislik, Elektrik ve Elektronik; Endüstri Mühendisliği; Mühendislik, Makine; Malzeme Bilimleri, Biyomalzemeler